Home buyers' purchase decision framework for Klang Valley, Malaysia - Mang, Jie Sheng (2021)
To solve the property overhang issues in Malaysian housing market, housing developers require answers and solutions for housing attributes and services to increase their sales. However, previous researchers only focused on one aspect while studying house buyers' purchase-decision. So, to overcome the problems of property overhang and low satisfaction-level, this research aims to investigate the housingpurchase factors, homebuyers' demographic, purchase decision and satisfaction. The chosen research method is Quantitative method as there is a large sample of population. Finally, it has developed a Home Buyers' Purchase Decision Framework for the home buyers in Klang Valley. The researcher has collected data using SurveyMonkey, an online survey tool and has developed a questionnaire specifically to Klang Valley residents for their opinions on housing purchase factors, purchase decision and post-purchase satisfaction. A total of 417 questionnaires were returned from the 2,000 distributed. Then, the data was analyzed using logistic regression, multivariate analysis of variance and multiple linear regression. This result is then validated by 24 respondents to increase the accuracy. The findings show that home buyers’ purchase decision are influenced by all house purchase factors: house structure, spaces, finance, location, and neighbourhood. However, gender, marital status, and family income of home buyer do not influence house purchase decision and financial factors do not have significant influence on home buyers' satisfaction. The results will make contributions to the Malaysian residential housing industry, give the housing developers a wider comprehension of their consumers and lay a foundation for the housing industry to improve. For the recent years, this research is the only known study that develops homebuyers' purchase-decision framework for Klang Valley housing market. Thus, this study contributes to the knowledge of homebuyers decision-making processes for the housing market in Malaysia.